2019
DOI: 10.4103/ijd.ijd_130_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interventional pain management on treating postherpetic neuralgia

Abstract: Background: Herpes zoster (HZ) is identified to induce postherpetic neuralgia (PHN) which is difficult to cure. PHN-related pain brings patients not only physical discomfort but also mental depression and anxiety. Currently, the main purpose of PHN treatment is to reduce patients’ pain. Now treatment combining some international pain management and drug therapy has come up. Aims and Objective: This study aims to evaluate the effect of interventional management through m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In elderly patients, especially those with multiple concomitant diseases, the side effects of medications limit the use of analgesic drugs ( 11 ). Patients with intractable pain even after conservative treatment require invasive treatments ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In elderly patients, especially those with multiple concomitant diseases, the side effects of medications limit the use of analgesic drugs ( 11 ). Patients with intractable pain even after conservative treatment require invasive treatments ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study for PHN also confirmed the effectiveness and safety of pulsed radiofrequency in DRG, and achieved immediate effect, but it failed to significantly reduce the incidence of PHN. 7,8 Although pulsed radiofrequency can cause analgesia, there is no treatment for antiviral and immune system regulation at the target, which may be the main reason for its unsustainable efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al and others reported that the incidence of PHN was still not less than 10% after Herpes zoster patients treated with recombinant human interferon-α2b after paravertebral injection. 7 Although this method can effectively have antiviral effect and improve the immunity of patients, it cannot significantly reduce the incidence of PHN.…”
Section: Introductionmentioning
confidence: 99%
“… 4 PHN is associated with long-lasting neurohypersensitivity that can have undesirable mental consequences such as depression, fatigue and sleep disorders. 5 Therefore, improving therapeutic effectiveness, preventing the occurrence of PHN, and achieving rapid pain relief for patients with zoster-associated pain (ZAP) have been a focus of attention for pain physicians.…”
Section: Introductionmentioning
confidence: 99%